Prevalence of non-alcoholic fatty liver disease in overweight or obese adolescents - Lázaro Rodríguez, Herminia (2024)
This  study  aimed  to  determine  the  prevalence  of  non-alcoholic  fatty  liver  disease  in  overweight  and  obese adolescents in a high school in Trujillo in 2023. A descriptive, cross-sectional study was conducted, including adolescents of both sexes, aged 12 to 14 years, with excess weight. Those with chronic diseases or undergoing pharmacological treatment with hepatotoxic effects were excluded. Validated methods for anthropometric measurement and ultrasound evaluation were used. Out of 130 adolescents with excess weight, 23 were diagnosed with obesity. This includes 14 males (60.8 %) and 9 females (39.2 %), all of whom underwent a liver ultrasound. Out of the adolescents evaluated, 34.8 % had nonalcoholic fatty liver disease. These findings show that approximately one-third of adolescents with obesity had an ultrasound-confirmed diagnosis of non-alcoholic fatty liver disease. This highlights the importance of designing and implementing educational strategies to promote healthy eating and physical activity, both in adolescents and their caregivers, particularly for those diagnosed with non-alcoholic fatty liver disease.